Rational Design of Polymethine Dyes with NIR‐II Emission and High Photothermal Conversion Efficiency for Multimodal‐Imaging‐Guided Photo‐Immunotherapy - Ran, Xiao‐Yun; Chen, Ping; Liu, Yan‐Zhao; Shi, Lei; Chen, Xue; Liu, Yan‐Hong; Zhang, Hong; Zhang, Li‐Na; Li, Kun; Yu, Xiao‐Qi (Advanced materials (Weinheim), 2023)
Phototheranostics have emerged and flourished as a promising pattern for cancer theranostics owing to their precise photoinduced diagnosis and therapeutic to meet the demands of precision medicine. The diagnosis information and therapeutic effect are directly determined by the fluorescence imaging ability and photothermal conversion efficiency (PCE) of phototheranostic agents. Hence, how to balance the competitive radiative and nonradiative processes of phototheranostic agents is the key factor to evaluate the phototheranostic effect. Herein, molecules named ICRs with high photostaibility  are rationally designed, exhibiting fluorescence emission in the second near‐infrared window (NIR‐II, 1000–1700 nm) and high PCE, which are related to the strong donor–acceptor (D–A) interaction and high reorganization energy Noteworthily, ICR‐Qu with stronger D–A interaction and a large‐sized conjugated unit encapsulated in nanoparticles exhibits high PCE (81.1%). In addition, ICR‐QuNPs are used for fluorescence imaging (FLI), photoacoustic imaging (PAI), and photothermal imaging (PTI) to guide deep‐tissue photonic hyperthermia, achieving precise removal and inhibition of breast cancer. Furthermore, combined with α‐PD‐1, ICR‐QuNPs show huge potential to be a facile and efficient tool for photo‐immunotherapy. More importantly, this study not only reports an “all‐in‐one” polymethine‐based phototheranostic agent, but also sheds light on the exploration of versatile organic molecules for future practical applications. Polymethine dyes with second near‐infrared emission and photoacoustic imaging capability are synthesized by the electronic‐donor group regulation strategy, which demonstrates high photothermal conversion efficiency (PCE = 81.1%) as an antitumor stategy in vivo and in vitro under the multimodal imaging guidance; theoretical calculation reveals the structure regulation mechanism for the polymethine‐based phototheranostic agent to achieve an excellent PCE.